Effects and Influential Factors on the Performance of State Elementary School Principals in North Sumatra - Hambali, Hambali; Siregar, Marlina; Sulaiman, Sulaiman; Asiah, Nur; Makmur, Teuku; Ashlan, Said; Muchsin, Muchsin (Jurnal Ilmiah Peuradeun, 2024)
Many factors are projected to affect the success of elementary school principals. The basis of this research is the impact and factors that influence the central performance of the State Elementary School Principals in North Sumatra Labuhan Batu Regency, especially the variables of organizational culture, interpersonal communication, innovative behavior, work motivation, and performance of the elementary school principal. This research is quantitative research with ex post facto research. The variables analyzed were not controlled and modified by the researcher, but the facts were revealed based on measuring the symptoms that have been owned or testing what will happen. The path analysis technique was used to investigate the pattern of relationships between variables to know the direct and indirect effects between endogenous and exogenous factors. Research results indicated that the exogenous component that had more substantial direct effect on the principal’s work motivation was the innovative behavior of the principle, interpersonal communication abilities, and the relatively less influential variable was the school’s organizational culture. Meanwhile, exogenous characteristics that had more substantial direct effect on the success of school principals are the school’s organizational culture, the principal’s work drive, innovative conduct and the lowest interpersonal communication abilities.